The SOSIALISASI PROSEDUR DAN MANFAAT PENDAFTARAN TANAH BAGI MASYARAKA - Simanjuntak, Maria Ferba Editya (Jurnal Pengabdian Bukit Pengharapan, 2023)
The importance of land registration for the first time for land owners who have not been registered and the Government(BPN) as well as the current problems related to land registration for the first time for land owners who have not beenregistered are the topics of our dedication. Ownership of a certificate as proof of ownership of land rights has becomea very important matter for continuing socialization or awareness efforts for the community. Land registration for thefirst time is very important, because land parcels that have been registered will receive a certificate and have legalcertainty. Currently, the percentage of ownership of land parcel certificates from land registration for the first time inIndonesia is still low. In fact, people can use their land certificates as a support to obtain money, namely as collateralfor obtaining credit at banking institutions and to reduce the space for middlemen, speculators and land manifulators.The purpose of writing this article is to provide legal understanding and knowledge in terms of the practice of the landregistration system, provide legal understanding and knowledge in terms of theory and history of land registration. n socializing the procedures and benefits of land registration, among others: Submission of Socialization Materials fromresource persons to residents who attend the socialization of the land registration system, Questions and Answers fromresidents to resource persons related to socialization of community service. Land registration on land in Indonesia needsto be carried out an activity where socialization needs to be carried out, so that the community can be given their rightsin increasing their understanding and knowledge regarding land registration. Furthermore, it can be assisted in termsof understanding legal science, especially related to land law, namely the land registration system in Indonesia.